Pengembangan Video Animasi Berbasis Pendekatan Saintifik Pada Mata Pelajaran Ekonomi di Kelas X IPS SMAN 1 Grogol - Ristanti, Maulina Dwi; Sakti, Norida Canda (JEKPEND: Jurnal Ekonomi dan Pendidikan, 2021)
This research aims to apply animation video learning media as one of the alternative media in SMAN 1 Grogol. This type of research is Research and Development (R&D) research by applying Thiagarajan's 4D development model, including definition, design, development, and deployment. Design research using One Group Pretest-Posttest Design. The test subjects were students of class X IPS 1 SMAN 1 Grogol as many as 20 people. Data collection instruments using 1) material study and validation sheet, and media 2) student response questionnaire, 3) pretest and posttest questions. As for the results of the study obtained that: 1) the development of animation video learning media is declared feasible with the acquisition of 100% material validation percentage, and 100% media validation, 2) the results of the student response questionnaire obtained a percentage of 95%, 3) the learner's learning results obtained a percentage of completion of 90%, the result is an increase from the pretest results that have a percentage of completion of 35% only. So that the media of animation video learning based on scientific approach in economic subjects is declared feasible, effective, practical, obtains a positive response, and can improve learning outcomes to be used as a learning medium.